Economic Valuation of Mangrove Ecosystem Services in Mandah District of Riau Province - Hades Mandela; Achmad Fahrudin; Gatot Yulianto (Faculty of Fisheries and Marine Science, Brawijaya University, 2020)
Mangrove ecosystems become an important ecosystem for the community of Mandah district, this is because the community uses the mangrove ecosystem as a producer of mangrove wood, as well as a place to catch fish, shrimp, and crabs. Therefore, it is important to maintain the sustainability of mangrove ecosystems in multiple ways; one option is by providing an economic report regarding the mangrove ecosystem. The purpose of this study is to estimate the economic value of mangrove ecosystems. This research was conducted in Mandah District using the survey method. Data analysis using economic valuation by calculating the total economic value of mangrove ecosystem services, comprising: supporting services, provisioning services, regulating services, and cultural services. The results showed that the total economic value of mangrove ecosystem services which has an area of 31,007 Ha amounting to IDR 6,100,130,675,685/year or IDR 196,733,985/Ha/year consisting of the value of supporting services amounting to IDR 2,843,521,034,280/year, the value of provisioning services IDR 120,274,922,887/year, the cost of regulatory services is IDR 3,132,894,718,518/year, and the value of cultural services is IDR 3,440,000,000/year. The high economic value of regulating and supporting services indicates that the mangrove ecosystem has a high value of environmental services, so it needs to be preserved and the sustainability of the mangrove ecosystem to remain of high economic value.